KUALITAS PERENCANAAN PEMBANGUNAN DESA PARIT I/II KECAMATAN SUNGAI APIT KABUPATEN SIAK TAHUN 2014-2015 - Galih Ghozali Yusuf; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research is based on the quality of village development planning which is very important for the village in determining future development. In its implementation, there are obstacles such as community participation is still not maximal / up and down, and not yet in favor of the community, attendance of musrenbangdes participants dominated by village government and ineffective development proposal in musrenbangdes. This study aims to describe the quality of village development planning and find out the ineffective development priority proposals. The method used in this research is descriptive approach method with qualitative research type. The type of research data is primary data and secondary data. Data collection techniques in this study are interviews and documentation. Technical analysis of data used is descriptive qualitative data analysis.The results show that the quality of village development planning is still not good. This can be seen from some data obtained from the villages, districts, and field data collected. The right solution to overcome these problems is the need for support from the village government in increasing the participation of the community both the socialization and the direct plunge of the field and the need for the provision of understanding in the form of motivation to the community to be more active in issuing opinions or proposals in accordance with the wishes and needs of society ..Keywords: Quality, Village Development Planning.